Hand Leiomyoma with Postoperative Heterotopic Ossification: A Case Report and Review of the Therapeutic Approach - Silva, Nuno Matos; Rodrigues, Sara; Baptista, Francisco; Sousa, João Marçal de; Lança, Pedro; Araújo, Teresa Clode de; Figueiredo, João (Brazilian Journal of Case Reports, 2026)
We present a 42-year-old left-handed female healthcare worker with Factor V Leiden coagulopathy who sustained direct trauma to her left hand and subsequently developed a soft tissue mass of the fourth finger. Surgical excision yielded a histopathological diagnosis of leiomyoma (smooth muscle actin-positive, S100-negative). Postoperatively, she developed heterotopic ossification (HO) with fixed 90-degree flexion contracture of the proximal interphalangeal (PIP) joint, requiring a second surgical intervention. Despite successful HO excision with initial restoration of full extension, progressive PIP contracture recurred secondary to pulley discontinuity and capsuloligamentous fibrosis. Chronic neuropathic pain necessitated multidisciplinary pain clinic involvement with partial response to pregabalin, tapentadol, and topical capsaicin. At two years after the second surgery, a persistent 30-degree PIP flexion contracture and refractory pain remain. This case illustrates the diagnostic complexity of hand soft tissue tumors, the risk of severe postoperative complications, and the importance of long-term multidisciplinary follow-up.